Unequal Infrastructure Development (Case Study in Banjarnegara District) - Wiwik Prihatin; Evi Gravitiani (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
This study will discuss the inequality of infrastructure development in terms of various aspects such as road conditions, clean water, solid waste, education, worship, and health. The purpose of this research is to determine the condition of infrastructure development that is not evenly distributed in the Banjarnegara district so that a strategy can be formulated to overcome this problem. The method used is descriptive qualitative using primary data obtained directly through a survey to show how the state of the existing infrastructure and secondary data. The results of this study indicate that inequality in infrastructure development occurs in almost all aspects. Three important and main aspects that must be addressed immediately are related to the construction or repair of road infrastructure because it is the mobility for all community movements to carry out their activities to make it smooth and easy, so that the development of an area is also easy to do. The second is increasing the number of clean water connection service coverage, and the third is handling solid waste management. If this is not done immediately, it will lead to even wider inequality in infrastructure development in the Banjarnegara district considering that infrastructure is also the key to driving economic growth and improving the quality of people's welfare.